Plan de negocio para la comercialización de productos derivados de las plantas medicinales en el cantón La Maná, año 2015 - Cevallos Moreira, Rita Anabel (2016)
Medicinal plants have been part of the culture for millennia; however the benefits of derived products have not been utilized optimally by the population of La Mana due to the lack of promotion; so it became necessary to design a business plan for the development and marketing of medicinal aromatic chamomile tea and lemon verbena for medicinal purposes; by performing a detailed market study through surveys directed towards consumers and traders of the product. The results indicated preferences in terms of aroma, price, presentation and frequency of consumption that are fundamental data to determine supply, demand and prices; the description of the manufacturing process of aromatic tea, location, plant layout and availability of resources are detailed in the economic study; Through marketing mix was stablis strategies to highlight the medicinal benefits of chamomile and lemon verbena settled. The economic and financial study detailing the requirements to implement the project, which requires an initial investment of $ 68.643, 69; which will be financed by contributions from shareholders and a bank loan. The NPV calculation allowed to determine the next value $ 22.056,04 and an IRR of 24% greater than zero, whereupon it was established that due to the considerable amount of the initial investment profitability decreased in the early years, however, the proposal is feasible so its implementation is recommended.